1990
DOI: 10.1136/oem.47.5.338
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activity in workers exposed to benzidine and beta-naphthylamine.

Abstract: To investigate the effects of benzidine (BZ) and /I-naphthylamine (BNA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These findings are of interest because no other immunological activity has been demonstrated in cancer patients except for NK activity, which was shown to be depressed at an early stage of cancer. NK cells play an important role in immune surveillance against tumors (Herberman, 1982), and suppression of NK activity is related to canceration (Tanigawa et al, 1990). AMLR might also reflect immune surveillance against tumors and the disturbance of self-recognition manifested by suppression of the AMLR might be related to the canceration.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are of interest because no other immunological activity has been demonstrated in cancer patients except for NK activity, which was shown to be depressed at an early stage of cancer. NK cells play an important role in immune surveillance against tumors (Herberman, 1982), and suppression of NK activity is related to canceration (Tanigawa et al, 1990). AMLR might also reflect immune surveillance against tumors and the disturbance of self-recognition manifested by suppression of the AMLR might be related to the canceration.…”
Section: Discussionmentioning
confidence: 99%
“…Benzidine and b-naphthylamine have been implicated as triggers for transitional cell metaplasia predisposing to the development of bladder cancer. One study of workers exposed to these chemicals reported increased circulating NK cells, but decreased function, in these subjects compared to normal controls [7]. Other conditions associated with diminished NK function include pregnancy [92], psychiatric depression [6], thermal injuries [93], strenuous exercise [94] and malignancy [95][96][97].…”
Section: Role Of Nk Cells In Viral Infections In Humansmentioning
confidence: 99%
“…Mounting evidence suggests that these cells are important in the early response of the immune system to many viral infections [1]. Although acquired deficiency in NK function has been described in the chronic fatigue syndrome (CFS) [2], human immunodeficiency virus (HIV) infection [3], metastatic carcinoma [4], autoimmune disorders [5], depression [6] and exposure to occupational chemicals [7]; the clinical significance of the reduced NK function in these disorders has not been established. The Chediak-Higachi syndrome [8] and leucocyte adhesion deficiency [9] are genetic disorders characterized by profiles of depressed immune response, each of which includes a depression of NK-cell function.…”
Section: Introductionmentioning
confidence: 99%